Empowerment of Karang Taruna through Training on the Upcycling of Container Wood Waste into Wall Lamps - Awang Eka Novia Rizali; Ariani Ariani; Elda Franzia Jasjfi; Resky Annisa Damayanti; Mahsa Raffa Raffa Luthta; Siti Marshaula Lyravega (Universitas Lambung Mangkurat, 2024)
Karang Taruna of RT. 10 RW. 005 Kedoya Selatan Village, Kebon Jeruk District, West Jakarta, is a platform for the development of the youth with the objective of promoting social welfare within the community. The results of field observations indicate that Karang Taruna RT. 10 RW. 005 Kedoya Selatan Village does not currently have any productive activities that are focused on the development of the potential of its members and the community in its vicinity. The Community Service team at the Faculty of Fine Arts and Design (FFAD) Trisakti University is motivated by this circumstance to offer training in order to empower the Karang Taruna in the region. The training is designed to instruct individuals on how to create wall lamps by upcycling container wood waste. This activity also seeks to educate participants on the process of converting container wood waste into functional products, in addition to developing their creativity and skills. The experimental method was employed in the preparation stage of this community service activity, while the mentoring method was combined with the PAR (Participatory Action Research) approach to actively engage the participants in the activities. The training session, which took place on Saturday, March 02, 2024, at the Materials and Processes Practicum Room at Trisakti University in West Jakarta, was attended by a total of 10 (ten) male participants between the ages of 17 and 26. The training resulted in the production of 10 wall lamps that functioned effectively and the enhancement of the skills, creativity, and knowledge of the members of Karang Taruna Kedoya Selatan regarding the management of container wood waste.